Growth Performance of Male Mojosari-Alabio Crossbred Ducks Fed Diets Containing Green Algae (Ulva fasciata delile) in Tropical Area - Dono, Nanung Danar (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was aimed to investigate the effectiveness of feeding local duks with green algae (Ulva fasciata delile) as alternative feed additive to maximize the growth performance in tropical area. Forty eight male day old ducks of Mojosari-Alabio Crossbred ducks were allocated to four dietary treatments, with tree replications with four ducks per replicate pen. The ducks were given one of four experimental diets: basal diet without additive supplementation (UF-0; control) or control diets with Ulfa fasciata delile (UF) supplementation with the levels of 10 g/kg (UF-1), 20 g/kg (UF-2), or 30 g/kg (UF-3), in tropical-opened poultry house. The diets and drinking water were provided ad libitum for 8 weeks rearing period. Variables observed in current study were: feed consumption, body weight gain, feed conversation ratio (FCR), slaughter weight, and income over feed and duck cost. The obtained data were statistically analysed using Oneway ANOVA. Duncan's new Multiple Range Test was subsequently used to separate data with significant difference. Results showed that 30 g/kg GA supplementation increased (P<0.05) body weight gain and slaughter weight, reduced feed conversion ratio (P<0.05), improved income over feed and duck cost (P<0.05), without affecting feed consumption. These results suggest that green algae migh be potential to be used as an alternative feed additive to maximize growth performance of male local Mojosari-Alabio ducks in tropical area.